Movers & fakers : an Alphas novel - Harrison, Lisi (Harrison, Lisi., 2010)
At OCD the losers are tormented. At Alpha Academy, they're sent home. Skye Hamilton has scored an invitation to the ultra-exclusive Alphas-only boarding school where beta is spelled LBR. What happens when the country's best, brightest, and hawtest begin clawing and scratching their way to the top?